2020
DOI: 10.1111/faf.12526
|View full text |Cite
|
Sign up to set email alerts
|

Ghosts of the deep – Biodiversity, fisheries, and extinction risk of ghost sharks

Abstract: Ghost sharks (subclass Holocephali) remain a largely data‐poor group of cartilaginous fishes. The general paucity of attention may partially be related to identification and unresolved taxonomic issues, occurrence in the deep oceans, and their low value and interest in fisheries (which some notable exceptions). Here, we synthesize and assess the extinction risk of all known extant ghost sharks (52 species) by applying the IUCN Red List of Threatened Species Categories and Criteria. Ghost sharks have a low prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 99 publications
0
37
0
Order By: Relevance
“…This was possible at the workshops focusing on subsets based on taxonomy (e.g., Sawfishes, Devil rays, Chimeras) or habitat (coastal, pelagic, deepwater). 32,[89][90][91] However, six skate species were assessed at the regional level in the Northeast Atlantic and Mediterranean and Black Seas (Blonde Skate Raja brachyura, Thornback Skate R. clavata, Smalleyed Skate R. microocellata, Spotted Skate R. montagui, Undulate Skate R. undulata and White Skate Rostroraja alba). This is because the West Africa workshops confirmed that these species have only a small fraction of their range in West African waters and are rarely captured in fisheries there.…”
Section: Geographic Scopementioning
confidence: 99%
See 1 more Smart Citation
“…This was possible at the workshops focusing on subsets based on taxonomy (e.g., Sawfishes, Devil rays, Chimeras) or habitat (coastal, pelagic, deepwater). 32,[89][90][91] However, six skate species were assessed at the regional level in the Northeast Atlantic and Mediterranean and Black Seas (Blonde Skate Raja brachyura, Thornback Skate R. clavata, Smalleyed Skate R. microocellata, Spotted Skate R. montagui, Undulate Skate R. undulata and White Skate Rostroraja alba). This is because the West Africa workshops confirmed that these species have only a small fraction of their range in West African waters and are rarely captured in fisheries there.…”
Section: Geographic Scopementioning
confidence: 99%
“…Most new assessments of Not Evaluated (NE) species result from the discovery and description of formerly unknown species, such as chimeras (Seafarer's Ghostshark Chimera willwatchi, Falkor Chimera Chimera didierae, and Robin's Ghostshark Hydrolagus erithacus, all DD). 91 While others result from the splitting of species, such as the separation of Flapper Skate (Dipturus intermedius, CR) from Common Blue Skate (D. batis, CR). 96 We find that, of the NE species assessed for the first time, more than one-quarter (26.3%, n = 45 of 171) are threatened, whereas roughly one-third (38.6%, n = 66) are LC, 11.7% (n = 20) are NT, and one-quarter are DD (23.4%, n = 40).…”
Section: Assessments Of Not Evaluated Speciesmentioning
confidence: 99%
“…Approximately one-third of chondrichthyan species are threatened due to overfishing as many are commercially exploited or caught accidently as by-catch (Dulvy et al, 2017(Dulvy et al, , 2021. For instance, the elephant shark (chimera) (Finucci et al, 2021), brownbanded bamboo shark (Fahmi et al, 2020), whitespotted bamboo shark (Chen et al, 2007), catshark, smalltooth sawfish (Yan et al, 2021), little skate (Curtis and Sosebee, 2015), and thorny skate (Pennino et al, 2019) (all species with available genomes), are commercially fished species which require management to avoid overexploitation. Molecular methods are fast becoming a mainstream tool in fisheries management and have already shown underrepresented or unregulated catch of chondrichthyan species through DNA barcoding and analyzing genetic population structure (Vargas-Caro et al, 2017;Kuguru et al, 2018).…”
Section: Genomics Resources and Conservationmentioning
confidence: 99%
“…Chimaera (i.e., ghost shark, order Chimaeriformes) population trends are unknown in the wider Caribbean, but chimaeras typically reside offshore, are caught as bycatch, and have little commercial value (Finucci et al, 2021). Globally, their contribution to total chondrichthyan catch is very low (Dulvy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%